THE ROLE OF LISTENING AND SPEAKING SKILLS IN ENGLISH LANGUAGE TEACHING (The Conference Hub, 2025)
Listening and speaking skills are the cornerstone of communicative competence in foreign language learning. Despite their critical role in ensuring effective interaction, these skills are often overshadowed by grammar and reading-focused curricula in non-native contexts. The aim of this research is to analyze the methodological approaches to enhancing listening and speaking skills in English language teaching, with a special focus on audiovisual resources, digital applications, and learner-centered strategies. The study is based on communicative, task-based, and constructivist approaches, emphasizing authentic input and meaningful output as vital conditions for competence development. Findings from pedagogical observation and research reveal that integrating audiovisual materials and interactive technologies improves learners’ comprehension, fluency, and confidence, while simultaneously fostering motivation and autonomy. The paper concludes with methodological recommendations for educators and highlights the long-term potential of technology-driven integration in developing communicative competence.